Elmondom, tehát vagyok: (Kamasz)identitás, bullying és menekülés a Tizenhárom okom volt című regényben és adaptációjában - Novák, Zsófia (Studia Litteraria, 2019)
Thirteen Reasons Why tells the story of Hannah Baker, a teenager who commits suicide, but leaves behind a number of audiotapes explaining her decision and the events that lead to it. The novel, and its recent adaptation into a series by Netflix are extremely popular; however, they have also been severely criticised by psychologists and mental health advocates for their portrayal of bullying and suicide. Reflecting on the issues raised by these experts, and placing Thirteen Reasons Why in the wider context of escapist fiction, in my article I analyse how power relations function between the adolescent characters, how their identity is affected by physical and mental abuse; and I attempt to draw conclusions as to whether Thirteen Reasons Why belongs in the category of “harmful fiction”.